Modeling combustion timing in an RCCI engine by means of a control oriented model. (April 2020) - Kakoee, A.; Bakhshan, Y.; Barbier, A.; Bares, P.; Guardiola, C.
Abstract: Reactivity controlled compression ignition (RCCI) engines as one of low temperature auto ignition combustion strategies have shown a good performance to reduce NO x and soot emission while increasing engine thermal efficiency. Combustion control of these types of engines is relatively complex because of their ignition type which makes it difficult to have a direct control on the start of the combustion. In this research, combustion phase of an RCCI engine was modeled with using a control-oriented method. The combustion properties such as start of the combustion, crank angle degree where 50 percent of the fuel is burnt(CA50) and the burn duration were modeled in this research. A modified knock integral model was used for start of combustion estimation. Using the effect of spontaneous front speed, burn duration was modeled where a mathematical model is developed; and Wiebe function is used to model CA50. Indicated mean effective pressure(IMEP) also estimated in this modeling. To validate the developed models, five experimental data sets from a heavy-duty RCCI engine were used. The results show the maximum mean errors of 1.7, 1.9 and 2.3 crank angle degree (CAD) for start of combustion, burn duration(BD) and the CA50, respectively and this quantity is 0.5 bar for IMEP in steady state condition. The transient condition of the engine operation was also investigated. The results and trends are promising in all characteristics of the combustion process especially in the modeling of the indicated mean effective pressure where the majority of the data have errors less than 1.5 bar. Highlights: Combustion characteristics of a six-cylinder Volvo RCCI engine were investigated. Control oriented model was used to estimate combustion characteristics. Delay time was considered as a function of performance parameters. Operational condition variations were intake pressure, EGR and gasoline fraction.